Lower limb joint work and joint work contribution during downhill and uphill walking at different inclinations. (16th August 2017) - Alexander, Nathalie; Strutzenberger, Gerda; Ameshofer, Lisa Maria; Schwameder, Hermann
Abstract: Work performance and individual joint contribution to total work are important information for creating training protocols, but were not assessed so far for sloped walking. Therefore, the purpose of this study was to analyze lower limb joint work and joint contribution of the hip, knee and ankle to total lower limb work during sloped walking in a healthy population. Eighteen male participants (27.0 ± 4.7 yrs, 1.80 ± 0.05 m, 74.5 ± 8.2 kg) walked on an instrumented ramp at inclination angles of 0°, ±6°, ±12° and ±18° at 1.1 m/s. Kinematic and kinetic data were captured using a motion-capture system (Vicon) and two force plates (AMTI). Joint power curves, joint work (positive, negative, absolute) and each joint's contribution to total lower limb work were analyzed throughout the stance phase using an ANOVA with repeated measures. With increasing inclination positive joint work increased for the ankle and hip joint and in total during uphill walking. Negative joint work increased for each joint and in total work during downhill walking. Absolute work was increased during both uphill (all joints) and downhill (ankle & knee) walking. Knee joint contribution to total negative and absolute work increased during downhill walking while hip and ankle contributions decreased. This study identified, that, when switching from level to a 6° and from 6° to a 12° inclination the gain of individual joint work is more pronounced compared to switching from 12° to an 18° inclination. The results might be used for training recommendations and specific training intervention with respect to sloped walking.